PEMANFAATAN SERBUK KAYU SEBAGAI MEDIA BERKARYA RAGAM HIAS PADA SISWA KELAS VII SMP NEGERI 2 JEPARA - Albertian, Fahmi Tanjung (Eduarts: Jurnal Pendidikan Seni, 2016)
The research reveals a problem: (1) how the use of serbuk kayu as ornament creation media in seventh graders of SMP Negeri 2 Jepara ?, (2) how is the result of serbuk kayu as ornament creation media seventh graders of SMP Negeri 2 Jepara ?. This research method uses development research conducted through observation of control. Data collected through observation, interviews, and documentation. The data analysis was done through data reduction, data presentation, and verification. Based on the results of the study, the first use of serbuk kayu as working media in teaching ornament in seventh graders of SMP Negeri 2 Jepara consists of objectives, materials, media, strategy, and evaluation. The material presented include ornament techniques and procedures ornament creation media. The learning method uses the scientific method. Learning evaluation consisted of reviewing spiritual attitudes, social attitudes, competence knowledge, and skill competence. Second, based on the results of the use of serbuk kayu as ornament creation media in seventh graders of SMP Negeri 2 Jepara obtained classification design works on control observation I and control observation II. In control observation I, as much as 2 students or 6% make trubusan design, two students or 6% make ceplok flower, 3 students or 8% made suluran design, and 29 students or 80% create floral design. In control observation II, as many as 1 students or 3% make ceplok flowers and 35 students or 97% create floral design.Â